2021
DOI: 10.1186/s12893-021-01381-2
|View full text |Cite
|
Sign up to set email alerts
|

The influence of primary and subsequent limb amputation on the overall rate of limb amputation in Saskatchewan, Canada, 2006–2019: a population-based study

Abstract: Background Understanding trends in limb amputation (LA) can provide insight into the prevention and optimization of health care delivery. We examine the influence of primary (first report) and subsequent (multiple reports) limb amputation on the overall (all reports) rate of limb amputation in Saskatchewan considering amputation level. Methods Hospital discharged data associated with LA from 2006 to 2019 and population estimates in Saskatchewan wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Per our study data, the second leading cause of LA in Saskatchewan was PVD, followed by trauma [30]. This clearly indicates that besides diabetes, the impact of PVD and trauma on LA incidence in Saskatchewan cannot be underestimated [30]. In contrast, in other jurisdictions, trauma accounted for most of the LA incidence [31].…”
Section: Plos Onesupporting
confidence: 52%
See 1 more Smart Citation
“…Per our study data, the second leading cause of LA in Saskatchewan was PVD, followed by trauma [30]. This clearly indicates that besides diabetes, the impact of PVD and trauma on LA incidence in Saskatchewan cannot be underestimated [30]. In contrast, in other jurisdictions, trauma accounted for most of the LA incidence [31].…”
Section: Plos Onesupporting
confidence: 52%
“…Furthermore, two Canadian studies; one based on the present data and the other based on Canadian national data, found diabetes as the leading cause of LA in Canada and in Saskatchewan, with a prevalence of 65-80% [7,30], respectively. Per our study data, the second leading cause of LA in Saskatchewan was PVD, followed by trauma [30]. This clearly indicates that besides diabetes, the impact of PVD and trauma on LA incidence in Saskatchewan cannot be underestimated [30].…”
Section: Plos Onementioning
confidence: 51%
“…3 Further, Littman et al found substantial geographical and ethnoracial variation contributing to SLA rates after minor (below the level of the ankle) amputation with greater risk among African American patients than white patients and those living in the southeast region of the United States compared to other regions. 12 In Saskatchewan, the rate of SLA (10.6 per 100,000 population) is steadily rising with a 3.2% average annual percent change from 2006−2019 13 ; this, in combination with a 45% provincial increase in overall diabetes prevalence over the last decade, 14 leads to the question of how epidemiologic correlates impact the rate of SLA in the province.…”
Section: Introductionmentioning
confidence: 99%
“…In Saskatchewan, the rate of SLA (10.6 per 100,000 population) is steadily rising with a 3.2% average annual percent change from 2006−2019 13 ; this, in combination with a 45% provincial increase in overall diabetes prevalence over the last decade, 14 leads to the question of how epidemiologic correlates impact the rate of SLA in the province.…”
Section: Introductionmentioning
confidence: 99%